SISTEM PENGEMBALIAN OBJEK TANAH SITAAN PADA PENGADILAN NEGERI KOTA BANDA ACEH: SUATU KAJIAN HAK AL-MILKIYAH DALAM FIQH MUAMALAH - Cut Yustianiansyah; Azka Amalia Jihad (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This article aims to examine the system of returning confiscated objects at the Banda Aceh city district court according to the perspective of Al-Milkiyah Rights in Muamalah Jurisprudence. The approach taken by the author is juridical-empirical research. The main data is obtained from interviews with the parties, and a number of applicable laws and regulations, while secondary data is obtained from the results of research related to this research. The results showed that the system for returning confiscated objects was carried out based on the provisions of the SOP. In the decision of the Banda Aceh District Court No.64/Pdt.G/2020/PN Bna, the decision of the Banda Aceh High Court No. 72/PDT/2021/PT BNA, the decision of the Supreme Court of the Republic of Indonesia No. 4173 K/Pdt/2022 regarding unlawful acts, namely the Defendant occupying and obstructing the plaintiff to take control of the disputed land that he had obtained from the winning auction No. 533/01/2020, and the execution respondent did not voluntarily vacate the land, then the granting of the request for execution will be executed by force with the execution agency. The judge ordered the Registrar of the Banda Aceh District Court and bailiffs accompanied by two witnesses to carry out execution against the land in order to ensure law enforcement by handing over the object of the land plot to the applicant for execution by order of the judge. From this decision, it was decided to carry out the execution of the land to fulfill the decision that has permanent legal force. The land object in dispute must be returned based on an inkrah court decision for certainty of law enforcement.